Fiqh Digital: Mengurai Tantangan Hukum Islam Dalam Era 5.0 - Andi Ahsan Taqwim; Rahmatiah HL; Abd. Rahman R (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Technological developments in the Era 5.0 have brought fundamental changes to various aspects of life, including the methodology of Islamic law. This article addresses two main focuses: the implementation of artificial intelligence (AI) in contemporary ijtihad and the ethics of digital information dissemination from the perspective of Islamic law. Using a qualitative approach based on a literature review, the study shows that AI has significant potential to assist the process of legal through big data analysis, natural language processing, and more efficient management of shariah literature. Nevertheless, AI has epistemological limitations and cannot replace the role of the mujtahid, which requires fiqhiyyah intuition, an understanding of maqasid al-shariah, and moral judgment. On the other hand, the digital era demands the application of information ethics, particularly the principle of tabayyun and the concept of “filter before sharing,” in order to prevent the spread of hoaxes, slander, and distortions of religious teachings in the public sphere. The findings affirm that the integration of technology into Islamic law must be conducted selectively and ethically, while remaining oriented toward the public good (maslahah). Thus, synergy between digital innovation and shariah values is key to maintaining the relevance and authority of Islamic law amid modern technological developments.